A4NH research informs the design of a $13 million donor investment in improving food safety in six countries in Africa and one state in India - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The Bill & Melinda Gates Foundation and the UK Department for International Development used cumulative ILRI evidence on food safety burden and management in informal markets to shape their first joint investment in food safety. In response to the call, six grants totalling $13 million were awarded. Evidence-based interventions will be tested at a large-scale, potentially reducing food-borne disease risks for millions of consumers in Ethiopia, Burkina Faso, Kenya, Mozambique, Nigeria, Tanzania and one state in India.